PELATIHAN MANAJEMEN WAKTU PROYEK KONSTRUKSI BERBASIS APLIKASI MICROSOFT PROJECT PADA SISWA SMA/SMK - Avisha Gita Prafitasiwi; Kholidia Ayunaning; Rahmat Dwi Sutrisno; Rizki Alfianidah; Dewa Leowanda (DedikasiMU : Journal of Community Service, 2023)
The era of digitalization forces us to create a well-integrated system, thus the use of applications can facilitate the process of implementing and controlling work. In large-scale construction projects with a lot of project activities in it, it is impossible to control manually, so it will be easier if we use assistive applications such as Microsoft Project. The problem underlying the implementation of this training for SMA/SMK students is the lack of skills of the younger generation in using the application, especially in construction project time management. Application that are usually used in SMA/SMK are usually limited to Microsoft Excel. This service aims to increase the knowledge of students, especially SMK PGRI 1 Gresik students, so they can quickly adapt to the professional world. The presentation method, question and answer, pre-test, post-test and continued with practice are used in this cummunity service. The result of this training is an increase in the target of student knowladge from 55% to 86%.